Handling ready time uncertainties in dispatching automated guided vehicles to minimize job tardiness in container terminals - Ng, Jun Hao (2015)
In container terminals, they are many different types of container handling equipments. They must operate harmoniously to improve the ship operation. Besides the yard crane and quary crane, auto guided vechicle (AGV) is also one the of container handling equipments which plays an important role in transferring containers between quayside and yard. Thus job assignment to vehicle is very crucial as it affects the vessel turnaround time. But in order to assignment job to vehicle, the cost of the assignment has to be known. This can be calculated based on these few factors such as avaliable time of AGV, service time of the job,travel time of AGV and the deadline of the job. However factor such as AGV avaliable time is uncertain so the estimated assignment cost is not accurate in real time situation. The uncertainty setting is depicted by probability distribution. This project examines a method to make real-time decision when the ready time of a certain vehicle is known to differ from the expected ready time after the vehicle dispatching plan has been computed.